Modeling psychological well‐being among abdominal and pelvic cancer patients: The roles of total pain, meaning in life, and coping. Issue 11 (4th October 2022) - Krok, Dariusz; Telka, Ewa; Zarzycka, Beata
Abstract: Objective: Relationships between pain and well‐being are mediated by a variety of factors. This study examines a serial mediating role of meaning in life and coping in the relationship of total pain with psychological well‐being in abdominal and pelvic cancer (APC) patients. Total pain is understood in terms of physical, psychological, social, and spiritual components interacting upon one another. Methods: Adult patients diagnosed with the APC ( N  = 333) who were undergoing radiotherapy/chemotherapy treatment in two inpatient units of university hospitals completed questionnaires measuring total pain, psychological well‐being, meaning in life, and coping. SEM analysis was used to examine serial mediation effects. Results: All the dimensions of total pain were negatively associated with presence of meaning, coping strategies, and psychological well‐being. In contrast, the pain dimensions were positively associated with search for meaning. Presence of meaning, search for meaning, emotion‐ and meaning‐focused coping were serial mediators in the relationship between total pain and psychological well‐being. Conclusions: Our results strongly suggests that a holistic examination of pain among patients with cancer is important for several reasons. They also indicate that psychological well‐being is significantly influenced by the serial interplay of personal meaning structures and coping abilities.